Governing Global Health Care: A Case Study of India vis à vis Swirtzerland’s Novartis AG Regarding Patent of Gleevec - Novita Putri Rudiany (Jurnal Hubungan Internasional, 2017)
India has been acknowledged as the pharmacy of the world because of its developed pharmaceutical industries which produce many kinds of medicine for any diseases. However, this condition does not make the government close the opportunities for foreign manufactures to sell their products for the citizens. One of the foreign industries is the Switzerland’s company, named Novartis AG, selling Gleevec, a leukemia-treating drug. In 2013, Novartis AG proposed to renew the patent of Gleevec because it has been updated from the last version of 1995, but Indian government rejected the patent rights of Gleevec based on the fact that the new Gleevec did not show any significant change for leukemia treatment. Based on the phenomenon, this paper examines about the dynamic of governing the global health with India as the case study. There are three perspectives that are used, those are: rejectionism, transnationalism and institutionalism. Each of the perspective focuses on the three discussions. It begins with the first part which explains the object that was being governed. The second part talks about the parties that have roles to govern. The third partelaborates on how those different parties governed the provision of the medicine production and distribution as the part of global health issue